2014
DOI: 10.1158/0008-5472.can-13-1315
|View full text |Cite
|
Sign up to set email alerts
|

Histone Chaperone CHAF1A Inhibits Differentiation and Promotes Aggressive Neuroblastoma

Abstract: Neuroblastoma arises from the embryonal neural crest secondary to a block in differentiation. Long-term patient survival correlates inversely with the extent of differentiation, and treatment with retinoic acid or other prodifferentiation agents improves survival modestly. In this study, we show the histone chaperone and epigenetic regulator CHAF1A functions in maintaining the highly dedifferentiated state of this aggressive malignancy. CHAF1A is a subunit of the chromatin modifier chromatin assembly factor 1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…The reproducibility of replicates was assessed by Pearson correlation and permutation tests (Figure S1A-D and Supplemental Experimental Procedures). Four of the top candidates in the screen, CENPE (Balamuth et al, 2010), BRD4 (Puissant et al, 2013), CHAF1A (Barbieri et al, 2014) and KDM4B (Yang et al, 2015) were already characterized as required for NB cell survival. We performed a validation screen using individual siRNAs against select candidate genes in SY5Y and BE2C (Figure 1C, for selection and validation criteria, see Supplemental Experimental Procedures).…”
Section: Resultsmentioning
confidence: 99%
“…The reproducibility of replicates was assessed by Pearson correlation and permutation tests (Figure S1A-D and Supplemental Experimental Procedures). Four of the top candidates in the screen, CENPE (Balamuth et al, 2010), BRD4 (Puissant et al, 2013), CHAF1A (Barbieri et al, 2014) and KDM4B (Yang et al, 2015) were already characterized as required for NB cell survival. We performed a validation screen using individual siRNAs against select candidate genes in SY5Y and BE2C (Figure 1C, for selection and validation criteria, see Supplemental Experimental Procedures).…”
Section: Resultsmentioning
confidence: 99%
“…166 Furthermore, MASH1 , PHOX2B , Hand2 BMP4 and other genes are known to have critical roles in chromaffin, dorsal root and sympathetic neural development. 167,168 More recently, studies in zebrafish have confirmed that PHOX2B is required for normal development of neural crest-derived cells that comprise the sympathetic ganglia, 136 and that specific PHOX2B aberrations can have varying effects on differentiation. 169 Additional studies could potentially clarify if PHOX2B and other genes involved in neural crest development have a role in neuroblastoma regression as well.…”
Section: Neuroblastoma—spontaneous Regressionmentioning
confidence: 99%
“…Epigenetic changes affecting expression of genes relevant to neuroblastoma development were initially reported more than a decade ago, 134,135 and several studies have suggested that alterations in gene methylation and histone modification are related to patient outcome (Figure 2). 136139 The correlation between epigenetic changes and neuroblastoma behaviour has been increasingly studied, particularly because next-generation sequencing analyses of neuroblastoma have reported a very limited number of previously unrecognized recurrent somatic mutations. 4144 Furthermore, data from other childhood tumour types, particularly Wilms tumour and medulloblastoma, suggest that epigenetic changes might help to explain poorly understood aspects of disease presentation and clinical behaviour.…”
Section: Mechanisms Of Spontaneous Regressionmentioning
confidence: 99%
“…To further support the hypothesis that upregulation of H3.1 facilitates cancer, several studies have reported increased levels of CAF-1 (chromatin assembly factor 1) in various cancer types [5964]. CAF-1 is a chaperone protein that guides histone H3.1 into the nucleosome at S-phase in a replication-dependent manner (1).…”
Section: Polyadenylated H31 Mrna Leads To Cell Transformationmentioning
confidence: 99%